CFO Gender, Corporate Risk-Taking, and Information Disclosure Violations - Zhao, Yujie; Xiong, Jiaxin; Wang, Jingjing; Ye, Nanji (Frontiers in Psychology, 2022)
The sex ratio at birth in China exhibits a major occurrence of “missing women” due to the high son preference in Chinese culture. Clearly, the large gender discrepancy in China can be explained not only by ethical, moral, or social fairness theories but also by the economic benefits of women's particular abilities, experiences, and talents. This article examines the influence of female chief financial officers (CFOs) on information disclosure violations in order to highlight women's positive contributions. Our data imply that having a female CFO can dramatically lower the number of companies that fail to disclose information. The results are strong after controlling endogeneity with propensity score matching, Heckman's two-stage self-selection model, and CFO change, as well as controlling the gender of the chairman and chief executive officer, utilizing different study periods, and using exogenous shock. We further examined the moderate effects of CFO power and external monitoring, and we found that CFO power magnifies the negative effect of female CFO on violations; the more the power, the more the negative effect of female CFO on violations. We also found that when the firm has effective external monitoring, there are fewer future infractions of information disclosure.